In Vitro and in vivo Test of Exctract of Morinda citrifolia and Allium sativum on Subclinical Mastistis Cows - Sufiriyanto, Sufiriyanto; Indradji, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
Two subsequent experiments were conducted in the current study. Experiment I (in vitro), milk obtained from sub-clinical mastitis dairy cows were used to identify the content of bacteria types causing mastitis. It was identified that the milk contained Staphylococcus sp (76.92%), Streptococcus sp (15.38%) and E. coli (7.69%). In order to determine the optimum combination of Morinda citrifolia (M) and Allium sativum (A) for reducing the number of the identified bacteria. The milk were randomly assigned to one of four treatments with six replicates in each treatment (Completely Randomized Designed). There were four treatments, which were four kinds of Morinda citrifolia (M) to Allium sativum (A) ratio, i.e. T1 (80:20); T2 (60:40); T3 (40:60); and T4 (20:40). Collected data were analysed using analysis of variance. When analysis of variance indicated significant effects, Least significant different (LSD) was then employed.Â It is indicated that T1 was the most optimum treatment to reduce bacteria counts. Experiment II (in vivo), the purpose of the experiment was to detemine the optimum dose of T1 to cure sub-clinical mastitis dairy cows and to investigate the effects of different doses of T1 on milk quality.Â A total of 20 sub-clinical mastitis dairy cows were randomly treated with one of five treatments for 3 days, which were C (received penicillin), P1 (received T1:100 ml/d); P2 (received T1:200 ml/d); P3 (received T1:300 ml/d) and P4 (received T1:400 ml/d). Analysis for variance was applied followed by dunnetâs test. Milk production and somatic cell counts were not significantly (P>0.05) affected by the treatments, but they significantly (P<0.005) influenced milk dry matter content. Dairy cows treated with P4 produced milk with the highest dry matter content (11.92 Â± 1.90%). In conclusion, The mixtures ofÂ Morinda citrifolia and Allium sativum can cure mastitis and improve milk dry matter content. (Animal Production 7(2): 101-105 (2005)Â Key Words: Mastitis, Dairy cattle, Allium sativum, Morinda citrifolia, Quality of milk